DEVELOPMENT OF PUBLISHING BUSINESS IN TALLINN IN THE 18TH CENTURY - REIMO, TIIU (Knygotyra, 2014)
The aim of the article is to give an overviews of the development of publishing business in the 18th century Tallinn. It presents the most important groups of publishers and characterises their publishing articles. The article also analyses how the main characteristic features of European publishing of the time (subscription, authorship rights, contracts with authors) were adapted in Estonian publishing activities. KEYWORDS: book history, publishing, the 18th century, Tallinn, printer-publishers, booksellers, bookbinders, publishing companies, subscription, censorship.